Cultural Policy of Yugoslav Self-Management: Conceptual and Value Bases and Modalities - Kolarić, Vladimir M.; Vukićević, Vuk B. (Sociološki pregled, 2019)
The paper points to the importance of culture in the project of Yugoslav socialist self-management and explores, in the frst place, the doctrinal interpretation of culture as a sector, an integrative factor of the socio-political system and conceptual-value regulator. Diﬀerent modalities of cultural policy are explored in the context of socialist self-management and a model of their classifcation is proposed, which could more clearly clarify the peculiarities of the cultural policy of socialist self-management and perceive their relevance for our time. Given the understanding of culture as an integral part of the project of establishing a socialist self-managing society, representing its “core”, the failure of the project of Yugoslav socialist self-management could be viewed not as a primarily political or economic one, but as a failure in the feld of culture. Keywords: socialist self-management, culture, cultural policy, Yugoslavia.